Righting the Police: How do Officers Make Sense of Human Rights? - Martin, Richard (The British journal of criminology, 2022)
Human rights have become a dominant paradigm in police reform projects worldwide, championed by policymakers, legislators and campaigners alike. Such projects are often premised on, and evaluated according to, a conception of human rights as an autonomous, coherent and legitimate body of norms. It is a paradigm made real through formal training, procedures and oversight. This paper invites a different reading of human rights. Drawing on extensive interviews with junior officers, it reveals how human rights come to be emergent from, and embedded within, the minutia of their working lives. The presence and meaning of human rights are sustained through a series of ‘sensemaking’ narratives arising from the rich intermingling of legal and organizational representations of rights and officers’ own experiences. Subtle variations, inconsistencies and contradictions in officers’ sensemaking are revealed across a four-fold typology which disrupts the stability and coherency of the human rights paradigm, but also generalizations made about police culture.